(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Strategic managementtechniques can be viewed as bottom-up, top-down or collaborative processes. Inthe bottom-up approach, employees submit proposals to their managers who, inturn, funnel the best ideas further up the organization. This is oftenaccomplished by a capital budgeting process. Proposals are assessed usingfinancial criteria such as return on investment or cost-benefitanalysis. Cost underestimation and benefit overestimation are majorsources of error. The proposals that are approved form the substance of a newstrategy, all of which is done without a grand strategic design or a strategicarchitect. The top-down approach is the most common by far. In it, the CEO,possibly with the assistance of a strategic planning team, decides on theoverall direction the company should take. Some organizations are starting toexperiment with collaborative strategic planning techniques that recognize theemergent nature of strategic decisions.